A Study on the Recurrent Processes of the Goddess and Her Representation: Hera - Cansın Okan; Rifat Eser Kortanoğlu (Anadolu Araştırmaları)
Throughout history, communities within the proximity of each other had developed economical, religious, political relations and cultural transmissions between them. From early periods, Aegean, East Mediterranean, and Mesopotamian cultures had leaned towards similar characters in terms of ritualistic, religious and cultic figures. Even though divine figures had a similar point of origin, their characteristics and significance had changed with the location and period. Transfer of the socio-cultural production is an outcome of the relation between the East Mediterranean and Anatolia since The Bronze Age. Mesopotamian mythos’, characters and their descriptions had been transferred through cultures, while, in the background, their essences preserved, reformed and told by Greek bards for ages. In this article, the traceable interaction process through the mythic and religious indicators of the socio-cultural formof Ancient Greek and as a minor print of this transformation Goddess Hera and eastern versions of her cultural structure had been analyzed.